Soil Organic Carbon Status of Indian forests - Velmurugan, A.; Kumar, Suresh; Dadhwal, V. K.; Gupta, M. K. (Indian Forester, 2014)
Soil organic carbon (SOC) is a major component of global carbon sinks and forests being one of the most important ecosystems for storing SOC. A database of SOC estimates along with other attribute information for different forest types of India were compiled from various literature sources and normalized for 1990 using modeling approach. Different thematic maps in digital format were prepared and harmonized using standard geospatial reference. The database was linked to thematic maps and used to estimate SOC densities and stock for three depth classes (0-25, 0-50 and 0-100 cm) in geographical information system. The mean soil organic carbon density estimates for top 30 cm ranged from 22.42 t/ha in sub-tropical dry evergreen forest to 100.33 t/ha in Himalayan moist temperate forest and similar trend was observed for top 0-50 and 0-100 cm as well. Soil organic carbon stock estimates for top 30 cm ranged from 1.89 Tg C in Himalayan dry temperate to 1406.68 Tg C in tropical moist deciduous forest and comparable trend was observed for top 0-50 and 0-100 cm. The total soil organic C pools in Indian forests have been estimated as 3.72, 5.25 and 7.66 Pg C in top 0-25, 0-50 and 0-100 cm soil depth respectively (1 Pg = 1000 Tg). The present database may form inputs in models to study carbon flux and help in prioritizing areas for carbon sequestration in Indian forests.